2019
DOI: 10.1021/acs.joc.9b00808
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spiro[indole-3,5′-isoxazoles] with Anticancer Activity via a Formal [4 + 1]-Spirocyclization of Nitroalkenes to Indoles

Abstract: An acid-assisted [4 + 1]-cycloaddition of indoles with nitrostyrenes affords 4′H-spiro­[indole-3,5′-isoxazoles] in a diastereomerically pure form. Several of these spirocyclic molecules exhibit promising anticancer activity by reducing viability and inducing differentiation of neuroblastoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Next, deprotonation at the adjacent carbon produces enamine species 8. Subsequent elimination of the phosphoryl moiety affords oxime 9, which, once formed, undergoes a 5-endo-trig cyclization to provide a spirocyclic iminium species 10, which was described in our previous report [18] (Scheme 3). If R 3 = H, a deprotonation may occur, leading to a more stable imine form 5, as shown in Scheme 1 (vide supra).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Next, deprotonation at the adjacent carbon produces enamine species 8. Subsequent elimination of the phosphoryl moiety affords oxime 9, which, once formed, undergoes a 5-endo-trig cyclization to provide a spirocyclic iminium species 10, which was described in our previous report [18] (Scheme 3). If R 3 = H, a deprotonation may occur, leading to a more stable imine form 5, as shown in Scheme 1 (vide supra).…”
Section: Resultsmentioning
confidence: 69%
“…We have previously reported that generation of the key 4 H-spiro[indole-3,5 -isoxazole] 5 [18,19] takes place under acidic conditions, while isomerization of the latter into nitrile 6 occurs in the presence of weak bases [20]. Arguably, activation of nitroalkane 4 toward the desired transformation requires generation of nitronic acid 3 (also known as aci-form), which occurs in a basic medium [18]. To test this idea, nitroalkane 4ba was refluxed in benzene in the presence of several carboxylic acids/triethylamine combinations (Table 1, entries 1,2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During our research involving nitrogen-based heterocyclic compounds [26][27][28] we got very enthusiastic about the possibility of employing synthetic equivalents of bis-electrophilic 3,4-dihydro-2H-pyrrol-1-ium-4-ylium synthon for expeditious assembly of bicyclic and tricyclic heterocyclic scaffolds. Although the structure of 5-hydroxy-1,5-dihydro-2H-pyrrol-2-ones 8 seems to be a suitable synthetic equivalent, lengthy and laborious synthetic approaches to these molecules rendered this idea cost-prohibitive and much less exciting.…”
Section: Resultsmentioning
confidence: 99%